PENERAPAN METODE TALKING STICK DALAM PEMBELAJARAN POLA KALIMAT BAHASA JEPANG (Studi Eksperimen terhadap Siswa Kelas XI SMA Taruna Mandiri Pekanbaru) - Wartati Wartati; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study descibe and explain the application of the Talking Stick method in learning Japanese sentence patterns in the students of class XI IPA 2 SMA Taruna Mandiri Pekanbaru. The purpose of this study is to know the Talking Stick method effective in improving the learning japanese sentence patterns in the students of class XI IPA 2 SMA Taruna Mandiri Pekanbaru after using the talking stick method. In this study, the writer used a weak experimental research design with marked by the absence of a class of comparison. The technique of collecting data by test. The test results are processed using wilcoxon test on SPSS software version 23. Average prestest score 54, Average posttest score 79. Thus, the talking stick method was effective in improving learning Japanese sentence patterns student learning outcomes of class XI IPA 2 SMA Taruna Mandiri Pekanbaru.Key Words: Talking Stick Method, Learningjapanese Sentence Patterns, Sma Taruna Mandiri